2002
DOI: 10.1038/sj.bjp.0704771
|View full text |Cite
|
Sign up to set email alerts
|

Role of adrenergic receptors in vascular remodelling of the rat choroid

Abstract: 1 Choroidal blood vessels, located between the sclera and retina, constitute the principle source of blood¯ow to ocular structures. The choroid is innervated by vasoconstrictor sympathetic and vasodilator parasympathetic nerves. 2 We have shown previously that sympathetic denervation for 6 weeks leads to signi®cant increases in choroidal thickness, percentage of choroid occupied by vascular lumina, and numbers of choroidal venules, large arterioles and outer retinal capillaries. Sympathetic dea erentation prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 20 publications
1
29
0
1
Order By: Relevance
“…In contrast, the outer band as measured by MRI was significantly thicker than the histological determination of the choroidal vascular layer. We found only a single report of choroidal thickness (25-45 m) determined by histology (21). The discrepancy between the in vivo and histologic data could arise from collapse of choroidal vessels after removal of orbits from the systemic circulation, histological shrinkage, and͞or PVE because of limited MRI spatial resolution, underscoring the importance of measurements in vivo.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, the outer band as measured by MRI was significantly thicker than the histological determination of the choroidal vascular layer. We found only a single report of choroidal thickness (25-45 m) determined by histology (21). The discrepancy between the in vivo and histologic data could arise from collapse of choroidal vessels after removal of orbits from the systemic circulation, histological shrinkage, and͞or PVE because of limited MRI spatial resolution, underscoring the importance of measurements in vivo.…”
Section: Discussionmentioning
confidence: 87%
“…Sympathectomy also produced significant increases in the number of choroidal venules and arterioles and the retinal capillaries in the outer nuclear layer (9). Additionally, we determined that the ␤-adrenergic receptor antagonist propranolol (which blocks ␤ 1 -and ␤ 2 -adrenergic receptors) produced changes in the choroid similar to those after a sympathectomy (10). Because the ␤ 3 -adrenergic receptor was thought to be found primarily in white and brown adipose tissues (11), we did not characterize the role of this receptor after sympathectomy.…”
mentioning
confidence: 90%
“…In addition, previous work in our lab also showed that in vitro stimulation with propranolol, a beta-adrenergic receptor antagonist, caused similar changes as those seen after surgical sympathectomy while the alpha-adrenergic receptor antagonist, phentolamine, produced no changes (Steinle 2002). Because treatment with propranolol caused changes that were similar to sympathectomy, and stimulation with the alpha-adrenergic receptor antagonist showed no changes, we hypothesized that stimulation with a beta-adrenergic receptor agonist may prevent retinal changes induced by diabetes.…”
Section: List Of Tablessupporting
confidence: 60%
“…Current studies in our lab have shown that Müller cells possess B 1 (Walker & Steinle 2007) and B 2 -adrenergic receptors subtypes, while REC possess B 1 and B 3 -adrenergic receptor subtypes (Steinle & Smith 2002). Stimulation of the beta-adrenergic receptors on the above-mentioned cell types elicited beneficial effects in the retina, such as reductions in inflammatory and apoptotic markers.…”
Section: Beta-adrenergic Receptors: the Retinamentioning
confidence: 93%
See 1 more Smart Citation